A note on transfer pricing and the R&D intensity of Irish manufacturing - Frank G Barry (University College Dublin, Department of Economics, 2002)
Ireland's low corporation tax regime has proved especially attractive to foreign multinational companies operating in high-tech sectors. Ireland's increasing concentration in such sectors has facilitated the country's rise in the international R&D rankings. On a sector by sector basis however, R&D expenditures in Ireland remain low by international standards. This has led to questions about whether the health of the country's R&D environment matches the technological orientation of its industry, and about the commitment of the foreign sector to R&D activities in host economies such as Ireland. The present note focuses on the transfer pricing behaviour that tends to arise in a low corporation tax regime, and shows that a simple correction for transfer pricing reveals Ireland to be less of an outlier in terms of sectoral R&D expenditures than the conventional measures suggest.
hdl:10197/1260
Keywords: 330; Transfer pricing; Multinational Corporations; R&D Intensity; Industrielle Forschung; Direktinvestition; Multinationales Unternehmen; Verrechnungspreis; Irland